Hypertrophic cardiomyopathy in combination with juvenile amaurotic idiocy. Chance or fundamentally related findings?. Issue 6 (June 1984) - Baandrup, U; Rosenskjold, B; Bjerregaard, P
Abstract : Hypertrophic cardiomyopathy and juvenile amaurotic idiocy (one of the ceroid lipofuscinoses ) were diagnosed in a 29 year old man. This combined finding may be one of pure coincidence, but hypertrophic cardiomyopathy like changes of the myocardium are known to occur in Friedreich's ataxia and lentiginosis . The occurrence may, therefore, indicate some fundamental interrelation.